Investigation of an outbreak of suspected food poisoning in a school - Pande, Bhanupriya S.; Chavan, Yuvaraj B. (International Journal Of Community Medicine And Public Health, 2019)
Background: An outbreak investigation for food poisoning in a school of rural Maharashtra was carried out. This school had central kitchen for children staying at hostel. During monsoon season occurrence of acute gastroenteritis diseases is common and hence it important to investigate each and every suspected outbreak presenting with similar symptoms to that of acute gastroenteritis. Methods: It was a retrospective and prospective study design. All 140 children who ate food from central kitchen were interviewed and followed up. Median incubation period was obtained from the 12 children who fitted into case definition which was given by integrated diseases control program of Maharashtra. Environmental and food sampling along with laboratory investigations was done for diagnosis. Results: Total 12 children had symptoms of food poisoning. The median incubation period was around 8 hours. Gastrointestinal symptoms were the commonest reported by all the 12 children. It was found out that all the symptomatic children had eaten laddu brought from outside and stored in unhygienic conditions. Conclusions: Eating of laddu which were stored in unhygienic conditions had resulted into growth of Clostridia streptofaecalis in it causing food poisoning to children.